2009
DOI: 10.1007/s12022-009-9097-8
|View full text |Cite
|
Sign up to set email alerts
|

RAS Mutation-Positive Follicular Variant of Papillary Thyroid Carcinoma Arising in a Struma Ovarii

Abstract: Struma ovarii is an ovarian mature teratoma composed exclusively or predominantly of thyroid tissue. Malignant transformation of struma ovarii is rare and poorly understood, although this process is thought to be similar to carcinogenesis in malignant tumors of differentiated thyroid tissue originating in the thyroid gland. Genetic alterations in the mitogen-activated protein kinase pathway, including mutations of BRAF, RAS, and RET genes, have been implicated in the development of differentiated thyroid carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Previous case series describe the presence of point mutations in BRAF, NRAS, HRAS , and RET/PTC rearrangements but none in the KRAS gene [6,15-17]. The present report therefore describes for the first time a KRAS codon 12 mutation in a case of PTC with a follicular growth pattern arising in SO in combination with bilateral teratoma [10-12].…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Previous case series describe the presence of point mutations in BRAF, NRAS, HRAS , and RET/PTC rearrangements but none in the KRAS gene [6,15-17]. The present report therefore describes for the first time a KRAS codon 12 mutation in a case of PTC with a follicular growth pattern arising in SO in combination with bilateral teratoma [10-12].…”
Section: Resultsmentioning
confidence: 59%
“…The real incidence of malignancy in SO is unclear because of its rarity but the existing literature indicates that 5%–10% of such tumors are malignant with papillary and less frequently, follicular carcinoma being the most common [1-4]. It is believed that malignant transformation of SO has similar molecular features with and its prognosis corresponds to that of malignant tumors originating in the thyroid [5,6]. The molecular pathogenesis of papillary thyroid carcinomas (PTC) is largely associated with genetic alterations in the RET-RAS-RAF-MAPK pathway usually caused by RET/PTC rearrangements (13%–43%) or activating point mutations in the BRAF (29%–83%) or RAS- family genes (0 %–21 %).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kondo et al reviewed the pathogenetic mechanisms of thyroid follicular cell neoplasia and found mutations of BRAF (29%–69%), RET (13%–43%), and RAS (0%–21%) are most commonly seen in adult papillary thyroid carcinoma; RET rearrangements are more prevalent in adult tumors associated with previous radiation exposure [14]. Celestino et al reported a case of follicular variant of papillary thyroid carcinoma in a struma ovarii with NRAS mutation (Q61R) and a PAX8-PPARc rearrangement which fitted well with the similar results seen in cervical counterpart [18] and Coyne and Nikiforov reported HRAS codon 61 mutation in a case of follicular variant of papillary thyroid carcinoma in a struma ovarii [19]. Papillary carcinomas harboring RAS mutation almost always have the follicular variant histology.…”
Section: Discussionmentioning
confidence: 66%
“…Malignant struma usually are treated surgically, and radioactive iodine may be effective in treating metastatic struma [ 44 ]. Although most patients with malignant struma do well, some have died from the disease, particularly if there was metastasis [ 45 ]. In a study of 88 cases of malignant struma ovarii, the survival rate was 89 % at 10 years and 84 % at 25 years [ 46 ] …”
Section: Fig 16mentioning
confidence: 99%